Análise da resistência à corrosão por pites em aços inoxidáveis lean duplex SAF 2304 e super duplex SAF 2507 soldados em diferentes condições pelo processo GTAW - OLIVEIRA, Raillan de Lucas Arruda de (2019)
Aggressive environments such as petrochemical, chemical, and pulp and paper industries, demand for materials with high mechanical and corrosion resistance. The dual-phase microstructure is the main characteristic of duplex stainless steels (DSS), composed of ferrite and austenite with similar volumetric proportions, combining the high mechanical strength of ferrite and the high corrosion resistance of austenite. However, in most industrial applications of DSS welding processes are used in manufacturing or maintenance, where localized heating can cause phase unbalance and affect the corrosion resistance of Weld Metal (WM) and Heat Affected Zone (HAZ). This research aims to analyze the resistance to pitting corrosion, according to method A of ASTM G48, of lean duplex SAF 2304 and super duplex SAF 2507 stainless steels welded under different welding conditions by GTAW (Gas Tungsten Arc Welding) process, considering the addition of 2.25% of N2 in the argon shield gas, autogenous welding and with high nickel addition metal and the influence of reheat of the first pass, keeping the heat input constant of 1 kJ/mm. The microstructures of WM and HAZ were analyzed by optical microscopy. For all welding conditions, a reduction of the volumetric fraction of the austenite in the WM and HAZ was observed in relation to the Base Metal (BM). With the overlap of passes, as well as the addition of nitrogen in the shield gas, the volumetric fraction of austenite in the WM and in the HAZ increased. The SAF 2507 stainless steel welded with addition of N2 in the argon shield gas and two passes presented higher resistance to pitting corrosion when compared to the other welding conditions analyzed, resisting up to 50 ± 2 ° C. The SAF 2304 stainless steel, under all welding conditions, was limited to ambient temperature of 23 ± 2 ° C for the test.